Can we provide evidence-based care for the elderly?. Issue 6 (December 1997) - Straus, Sharon
Abstract : This is becoming an urgent question as the population ages. In many developed countries, the proportion of very elderly is growing rapidly. From 1960 to 1990, the total U.S. population grew by 39%, whereas The number of persons ≥ 65 years of age increased by 89% and the number ≥ 85 years of age increased by 232% (1). By 2010, the number of Canadians > 64 years is expected to increase by 45% and the number > 85 by 125% (2). This is partly because the oldest members of the baby-boom cohort will have reached 65 years of age; 20 years later, they will join the oldest old (> 85 years). We need to assess and optimize our health care for this group. Can we extend the practice of evidence-based medicine (EBM) to the elderly? Is care of the elderly already evidence based?